Pengaruh Gaya Kepemimpinan Dan Motivasi Terhadap Kinerja Karyawan Di Pramana Watu Kurung Resort Ubud - Dewi, Ni Komang Ayu Trisna; Prayogi, Putu Agus; Trianingrum, Ni Nyoman Nidya (Universitas Triatma Mulya, 2024)
Employee performance is a major factor in increasing the productivity of an organization. However, unprofessional leadership styles often lead to differences in the treatment of local employees, which leads to social jealousy. In addition, delays in paying salaries and lack of briefings before and after work shifts also have a negative impact on employee motivation and performance. Declining employee performance will affect the resort's revenue and occupancy. This study aims to analyze the influence of leadership style and motivation on employee performance at Pramana Watu Kurung Resort Ubud. This study also aims to identify independent variables that have a dominant influence on employee performance. Data collection techniques include observation, documentation, interviews, and questionnaires with a total population of 62 employees. while the sample used as many as 50 employees is not included in Top Management. The results of statistical analysis and multiple linear regression show that leadership style and motivation have a positive and significant influence on employee performance. These two variables contributed 62.9% to employee performance, with the motivation variable having a more dominant influence (0.450>0.428). As a suggestion, Pramana Watu Kurung Resort Ubud is expected to provide encouragement and enthusiasm to employees, as well as establish a salary policy that is in accordance with standards and ensure that salaries are given on time. Thus, employees will be more motivated to complete their work optimally and with high quality. These measures are expected to improve overall performance and productivity at Pramana Watu Kurung Resort Ubud.